2018
DOI: 10.1142/s2010007818400055
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Taxation and Revenue Recycling on U.S. Industries

Abstract: This paper provides a detailed, cross-model analysis and discussion of the implications of carbon tax scenarios on changes in sectoral output, energy production and consumption and the competitiveness of the United States' economy. Our analysis focuses on the broad patterns apparent across models in both qualitative and quantitative terms at the sector level, with a focus Climate Change Economics, Vol. 9, No. 1 (2018) on energy-intensive, trade-exposed sectors. We identify how variations in carbon tax trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…In contrast, The ITC will decrease the EPE. This finding complies with Macaluso, Tuladhar et al (2018) who showed the carbon tax would induce the substitutions toward less carbon-intensive energy sources and production technologies. Hence, with less resources allocated, the production efficiency of the energy sectors will decrease.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, The ITC will decrease the EPE. This finding complies with Macaluso, Tuladhar et al (2018) who showed the carbon tax would induce the substitutions toward less carbon-intensive energy sources and production technologies. Hence, with less resources allocated, the production efficiency of the energy sectors will decrease.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, The ITC will decrease the EPE. This finding complies with Macaluso, Tuladhar [33] who showed the carbon tax would induce the substitutions toward less carbon-intensive energy sources and production technologies. Hence, with less resources allocated, the production efficiency of the energy sectors will decrease.…”
Section: Discussionsupporting
confidence: 90%
“…Results from ADAGE-US and other models in this study (Macaluso et al, 2018) show that emissions are most sensitive to the size of the carbon tax applied and relatively insensitive to how the revenue is recycled. Figure 2 presents baseline levels and percent changes in GHGs for four scenarios: lump-sum and lump-sum with capital tax rebates at $25 and $50, both growing at 5%.…”
Section: Emissionsmentioning
confidence: 73%